Intellectual capital, absorptive capacity and product innovation. Issue 3 (18th April 2017) - Engelman, Raquel Machado; Fracasso, Edi Madalena; Schmidt, Serje; Zen, Aurora Carneiro
Abstract : Purpose: The purpose of this paper is to study the influence of intellectual capital on a firm's absorptive capacity (ACAP), and of ACAP on product innovation. The authors argue that intellectual capital and other sets of intangible assets are mobilized by firms through dynamic capabilities such as ACAP. Product innovation is one of the results of this process. Design/methodology/approach: A quantitative study was conducted, including 500 firms of different sizes, industries and technological intensities located in southern Brazil. The validity of constructs and the theoretical model were confirmed by structural equation modeling. Findings: The authors found that intellectual capital does influence ACAP, albeit differently on each of ACAP's dimensions. Acquisition, assimilation and exploitation of knowledge are more decisively influenced by structural capital, followed by human capital. The ability of transformation of knowledge is evenly influenced by structural and human capital, and more moderately so by social capital. The results also showed that ACAP influences product innovation, but each of its dimensions demonstrated a different impact. Practical implications: This study helps practitioners to identify the development of a firm's intangible resources and its influences on product innovation. This characterization can serve as a benchmark for managers or private and public companies to define strategies and policies to stimulate innovation. Originality/value: Few studies present a theoretical discussion about the relationship between a firm's resources and ACAP's dimensions in broad empirical contexts or in emerging countries.